Phytotoxicity test of effluent and sludge from a rice parboiling industry - Lourenço, Vitor Alves; Nadaleti, Willian Cézar; Vieira, Bruno Müller; Corrêa, Érico Kunde; Fialho, Gustavo Sessa (Ciência e Natura, 2022)
The rice represents a great sector inside of Brazil's economy, witch around all the rice consumed in the country 25% is the parabolized type. It is known that the beneficiation process of this product involves a high generation of effluent with the high organic loads and elevated levels of nitrogen and phosphor. The effluent treatment stations of these industries rely on anaerobic digestion to reduce the organic matter content, accordingly they generate anaerobic sludge. The possibility of the use of anaerobic sludge, treated or not, in agricultural soil awakens the need for studies that assure its practice in a sustainable way to the environment. The phytotoxicity is characterized as a highly important analysis, since it presents a general idea of the complexity of the interactions of the different compounds present in the residue or effluent. Germination tests have been the most used to evaluate phytotoxicity. This study aimed to evaluate the phytotoxicity of crude effluent and untreated sludge from a rice parboiling industry using three types of seeds, watercress, lettuce and cucumber. Germination rates varied from 1.432±0.370% to 78.176±15.340% indicating biomass phytotoxicity.